DETERMINAN NILAI PERUSAHAAN DI INDUSTRI PROPERTY, REAL ESTATE, DAN KONSTRUKSI - Kurniasih Dwi Astuti; Rahman Safi’i; Nana Nofianti (Universitas Pakuan, 2020)
This study aims to determine the effect of dividend policy on firm value and the effect of corporate social responsibility disclosure (CSRD) on firm value. The population in this study were all companies in the property, real estate and construction industry in Indonesia and the sample was selected using purposive sampling method. The data analysis method used in this study is multiple linear regression analysis (Multiple Regression Analysis). The results showed that dividend policy has a significant effect on firm value and disclosure of corporate social responsibility has no significant effect on firm value. This shows that shareholders tend to assess dividend distribution information as well because it is directly related to the welfare of shareholders compared to CSR disclosure which will not necessarily affect the welfare of shareholders.